2013
DOI: 10.3346/jkms.2013.28.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Radial versus Trans-Femoral Intervention for the Treatment of Coronary Bifurcations: Results from Coronary Bifurcation Stenting Registry

Abstract: Trans-radial (TR) approach is increasingly recognized as an alternative to the routine use of trans-femoral (TF) approach. However, there are limited data comparing the outcomes of these two approaches for the treatment of coronary bifurcation lesions. We evaluated outcomes of TR and TF percutaneous coronary interventions (PCI) in this complex lesion. Procedural outcomes and clinical events were compared in 1,668 patients who underwent PCI for non-left main bifurcation lesions, according to the vascular approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…Major bleeding occurred in 76 patients (0.92%) among the 8,240 eligible patients in four studies . The odds of major bleeding were significantly lower in TRA compared to TFA (OR = 0.44; 95% CI = 0.27–0.69, I 2 = 0%, p = .0005; Figure a).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Major bleeding occurred in 76 patients (0.92%) among the 8,240 eligible patients in four studies . The odds of major bleeding were significantly lower in TRA compared to TFA (OR = 0.44; 95% CI = 0.27–0.69, I 2 = 0%, p = .0005; Figure a).…”
Section: Resultsmentioning
confidence: 96%
“…The initial search identified 6,066 publications that were screened at the abstract level, of which 337 reports were eligible for full‐text review after exclusion of duplicate and irrelevant studies. After full‐text review, 12 studies were included in the final analysis . Out of those 12 studies, four studies were propensity‐matched and one of the studies had subgroup analysis from the EXCEL trial .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies reported the advantages of the Glidesheath Slender (7 French) or 7.5-Fr sheathless guide catheter in complex PCI including the LM with high procedural success and low vascular complication rate, therefore, potentially could mitigate the disadvantages of sheath size that may come up with TR-PCI. 32 Gili et al 5 De Maria et al 16 Chung et al 17 Study design De Maria et al 16 Chung et al 17 Key inclusion/exclusion criteria • Previous coronary intervention to LM was excluded.…”
Section: Discussionmentioning
confidence: 99%